Analysis of heat transfer of different nanofluids flow through an abrupt expansion pipe - Kimouche, Abdelali; Mataoui, Amina; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2017)
Turbulent forced convection. of nanofluids through an axisymmetric abrupt expansion is investigated numerically in the present study. Finite volume method is used to solve the governing equations. All results are analyzed through the thermal and dynamic fields, particularly the evolutions of skin friction coefficient and Nusselt number. The influence of nanofluid's volume fraction and Reynolds number on this type of flow configuration was examined. The analysis is detailed for pure water and four nanofluids (Ag-water, Cu -water, CuO-water and Al2O3 -water). All results evidence an increase of average Nusselt number with increasing the volume fraction and Reynolds number. Two correlations of average Nusselt number are proposed. The first correlation expresses the average Nusselt number versus Reynolds number, volume fraction and the ratio of densities of solid particles to that of the base fluid (Nu) over bar Nu = f (Re, phi, rho s/rho f). The second one relates Reynolds number, volume fraction and the conductivity ratio of solid particle to that of the base fluid ((Nu) over bar = f (Re, phi, ks/kf)). (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Abrupt expansion; Nanofluids; Turbulent flow; Turbulence modeling; Forced convection